2017
DOI: 10.1155/2017/4101503
|View full text |Cite
|
Sign up to set email alerts
|

Application of Conductive Materials to Asphalt Pavement

Abstract: Snow-melting pavement technique is an advanced preservation method, which can prevent the forming of snow or ice on the pavement surface by increasing the temperature using an embedded heating system. The main scope of this study is to evaluate the impact of conductive additives on the heating efficiency. The electrical resistivity and thermal conductivity were considered to investigate effects of conductive additives, graphite, and carbon fibers on the snow-melting ability of asphalt mixtures. Also, the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…It is worth noting that, all the weights presented in Table 2, were calculated with the aid of SG values provided in Table 1. According to literature, conductive fillers can be incorporated in asphalt-based materials by following either dry [7], [27], [28] or wet [29], [30] mixing method. In dry mixing method, all 19 the components including the conductive filler are mixed at a temperature range of 150-160°C 20 [7], [27], and in wet mixing method, the conductive fillers are first blended with bitumen at an 21 elevated temperature range of 170-180°C [29], [30], and then the modified bitumen is mixed 22 with other components.…”
Section: Specimen Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that, all the weights presented in Table 2, were calculated with the aid of SG values provided in Table 1. According to literature, conductive fillers can be incorporated in asphalt-based materials by following either dry [7], [27], [28] or wet [29], [30] mixing method. In dry mixing method, all 19 the components including the conductive filler are mixed at a temperature range of 150-160°C 20 [7], [27], and in wet mixing method, the conductive fillers are first blended with bitumen at an 21 elevated temperature range of 170-180°C [29], [30], and then the modified bitumen is mixed 22 with other components.…”
Section: Specimen Fabricationmentioning
confidence: 99%
“…According to literature, conductive fillers can be incorporated in asphalt-based materials by following either dry [7], [27], [28] or wet [29], [30] mixing method. In dry mixing method, all 19 the components including the conductive filler are mixed at a temperature range of 150-160°C 20 [7], [27], and in wet mixing method, the conductive fillers are first blended with bitumen at an 21 elevated temperature range of 170-180°C [29], [30], and then the modified bitumen is mixed 22 with other components. Increasing the mixing temperature increases the oxidation of bitumen 23 [31]; as a result, to reduce the bitumen oxidation, dry mixing method was utilized in this study, and using a rotational viscometer -and following the ASTM D4402 standard [32] -the 1 minimum mixing temperature of PG 58-28 was determined as 145°C.…”
Section: Specimen Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vo, H.V. and Park [ 13 ], Tang et al [ 14 ] found that the cooperation of graphite and carbon fiber contributed to more remarkable thermal conductivity increments compared to their individual properties, after partially substituting mineral filler due to the formation of conductive networks in asphalt concrete. Furthermore, the effectiveness of various combinations of graphite, carbon black and carbon fiber for improving the thermal conductivity of solar harvesting and snow melting pavements was validated in the study of Bai et al [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (8) reported that conductive additives in powder form are added in much higher quantities than fibrous additives to bring the electrical conductivity to the same level. Bai et al (12) and Vo and Park (9) reported that graphite (powder form) is added into asphalt mixes in dosages of 5% to 20% by volume of asphalt binder. In the case of fibrous additives, Vo and Park (9) utilized carbon fiber dosages of less than 5% by volume of asphalt binder.…”
mentioning
confidence: 99%